Comparison of blood pressure of senior high school students in the inner and outer city of Medan - Johannes H. Saing; Ridwan M. Daulay; Rafita Ramayati; Rusdidjas Rusdidjas (Indonesian Pediatric Society, 2007)
Background Blood pressure (BP) in children and adolescentsdepends on multiple factors, both genetic and environmental suchas gender, age, body weight and height, obesity, life style,socioeconomic status, etc. Surveillance of families in Medan(2000) reported that the socioeconomic status in the outer citywas lower than in the inner city; other factors that influence BPof adolescents may also be different.Objective To compare the prevalence of hypertension betweensenior high school students in the inner and outer city of Medan.Methods A cross sectional study was conducted on 250 studentsselected randomly from four senior high schools in Medan, each2 schools from inner and outer city. This study was done betweenJune and August 2003. BP measurement was done in the morningat 08.00 – 12.00 o’clock before the subjects got exercises. BPmeasurements were done three times according to Task Force onBlood Pressure 1996 recommendation. The average of systolicand diastolic was considered as BP of the subjects.Results Systolic and diastolic BPs of the female students in theouter city (115.3/80.0 mmHg) were higher than those of thefemale students in the inner city (111.2/71.8 mmHg) and thedifference was statistically significant (P=0.008 and P=0.014),but not for the male students. The prevalence of hypertension inthe inner and outer city of Medan was 6.0% and 8.4%, respectively.Conclusions The prevalence of hypertension in the outer city wasabit higher than that in the inner city. The averages of systolicand diastolic BPs of female students in the outer city were higherthan those of the female students in the inner city of Medan.